Hubungan antara Komposisi Tubuh dengan Laju Pernapasan Setelah Recovery Pasca Harvard Step Test pada Mahasiswa Kedokteran - I Dewa Gede Yogananda; Tanjung Subrata; Made Dharmesti Wijaya (Aesculapius Medical Journal, 2023)
Abstract Empowering physical fitness becomes a challenge considering mobility restriction because Covid-19 pandemic situation which impacting the increasing of passive lifestyle. If such situation is not well handled, it could risk for obesity and cardiorespiratory disease. To prevent that, it’s crucial to find out the correlation between body composition towards someone respiratory rate recovery ability. This research was held to find out the correlation between body composition with after recovery respiratory rate on medical student that taking Harvard Step Test. This research was using correlative analysis method with cross-sectional design. Population from this research is Warmadewa Faculty of Medicine and Health Student (FKIK Unwar) that choosing Baswara Prada Medical Assistance Team (TBM-BP). The respondent was taken by total sampling method and recruiting 61 respondents. The results of univariate analysis using SPSS version 18 shows the highest proportion of body composition is in ‘fair’ category (55.7%). For initial respiratory rate, there is 8 people (13.1%) that having respiratory rate above normal range while for final respiratory rate the highest proportion is in 21-30 times/minute range (80.3%). The bivariate analysis result using Spearman correlation test shows positive but weak and insignificant correlation between body composition with after recovery respiratory rate (p = 0.097 and r = +0.215). It’s concluded that body composition could influencing physical fitness although it’s not the main factor. The students, public, and related institutions are expected to understand the important of physical exercise to empowering physical fitness and the next study also expected to more comprehensive to correlating various variable related to body composition and after recovery respiratory rate. Keywords: physical fitness, body composition, recovery of respiratory rate